The global guide to animal protection - Linzey, Andrew (University of Illinois Press, 2013)
Raising awareness of human indifference and cruelty toward animals, The Global Guide to Animal Protection includes more than 180 articles that survey the extent of worldwide human exploitation of animals. In addition to entries on often disturbing examples of human cruelty toward animals, the book describes attempts of courageous individuals--including Jane Goodall, Shirley McGreal, Birute Mary Galdikas, Bernard E. Rollin, and Roger Fouts--to challenge and change exploitative practices. Also included is a special foreword by Archbishop Desmond Tutu, urging readers to seek justice and protection for all creatures, humans and animals alike.